EFEKTIVITAS PERAN SATUAN RESERSE NARKOBA POLRES BUKITTINGGI DALAM MENGATASI PENYALAGUNAAN NARKOTIKA - Adi, Okriadi (UNES Law Review, 2018)
Narcotic is a substance or medicine that very important and needed to treat a certain disease. However, if misused or used not suitable with standard treatment will damage to personal or society especially young generation. Using of narcotic will make a big damage to the life and cultural values of a nation. Since October 2009, the government has approved the Law Number 35 Year 2009 about Narcotics. Based on this law, the Indonesian Police (Polri) changed the approach in eradicating narcotics. The Indonesian Police (Polri) is the front guard to fight the narcotic. The problem in this study are: First, how is the role of Narcotic Detective Unit of Bukittinggi Police in embracing narcotic in the law field of Bukittinggi Police? Second, how is the effective of the role of Narcotic Detective Unit of Bukittinggi Police in embracing narcotic in the law field of Bukittinggi Police? The approach uses in this research is the normative as the main approach and juridical empiric approach as support. The techniques of collecting data uses are field study by interviewing for the primary data and library study for the secondary data. Then, the data analyzed qualitatively in descriptive analysis form. From the research results obtained several conclusions: First, the role of Narcotic Detective Unit of Bukittinggi Police in embracing narcotic in the law field of Bukittinggi Police is implemented in the preemptive, preventive, and repressive roles. Second, the implementation of the role of Narcotic Detective Unit of Bukittinggi Police in embracing narcotic in the law field of Bukittinggi Police has been effective. It is proved by many cases of narcotic finished by the role of Narcotic Detective Unit of Bukittinggi Police in embracing narcotic in the law field of Bukittinggi Police year 2015 – 2017 are year 2015 there were 47 cases with 63 suspected, year 2016 there were 48 cases with 69 suspected and year 2017 there were 48 cases with 59 suspected.